Embracing the future: path transformation and system reconfiguration for self-driving cars in West Sweden. Issue 11 (2nd November 2019) - Miörner, Johan; Trippl, Michaela
ABSTRACT: The past years have witnessed a surge of academic interest into how new industrial paths are developed in regions. Transformation processes of existing regional industries have received less attention. This article focuses on radical innovation-based renewal processes of established paths and investigates how regional innovation systems are tackling challenges related to path transformation. Drawing on insights from the regional and technological innovation systems literatures, we develop an analytical framework that elucidates the relation between path transformation and system reconfiguration. The framework suggests that regional innovation system elements are created or adapted to (i) target the build-up of system functions regionally; (ii) link up to system functions in other locations, and (iii) transplant system functions from elsewhere. The analytical framework is applied to a case study of the transformation of the automotive industry in West Sweden towards self-driving cars. The empirical analysis provides support for the importance of the three types of system reconfiguration and emphasises the relevance of different types of assets. Furthermore, it highlights how actors tend to utilise previous networks and positions in global innovation systems rather than turning to the development of system functions regionally as the 'default option' of system reconfiguration.